DIFFERENT METHODS OF INFORMATION ENCODING - Abdujabborov Madaminjon Voxidjon o’g’li; Otabayeva Sevarakhon (European Journal of Interdisciplinary Research and Development, 2023)
This article discusses signal encoding, which can be achieved using various methods. It also provides information on both uniform and non-uniform encoding. Uniform encoding involves coding based on a single symbol such as "0" or "1". Non-uniform encoding, on the other hand, utilizes different representations within hardware or digital systems. This approach allows codes to be expressed in multiple forms, such as binary codes.